Japanese Small Type Coastal Whaling - Fisher, Sue (Frontiers in Marine Science, 2016)
2016 marks the 70th anniversary of the International Convention for the Regulation of Whaling (ICRW) as well as the 30th anniversary of the International Whaling Commission’s (IWC) moratorium on commercial whaling. It also marks three decades of effort by Japan to overturn this ban. Its strategy to circumvent the moratorium by issuing permits to kill protected whales for scientific research is famous—even the subject of a 2014 lawsuit at the International Court of Justice. Less well known is Japan’s strategy to overturn the ban by persuading the Commission to authorise a category of commercial whaling known as Small Type Coastal Whaling (STCW) that is conducted on minke and other small whales in Japanese waters but has never been regulated, or even formally recognised, by the IWC. For three decades Japan has sought STCW catch limits for four communities which it claims are still suffering distress as a result of the moratorium. While the Commission has rejected each proposal, mainly citing concerns that the commercial nature and purpose of STCW violates the moratorium, Japan has persisted, exhibiting great flexibility in its approach. Its tactics changed significantly in 2014; it no longer denied (or defended) the commerciality of the hunt, but argued that it is irrelevant since it sought only a small exemption to the moratorium which would remain intact for all other populations. This is a perspective on Japan’s evolving STCW strategy and the risk that lifting, or modifying, the moratorium would pose to the conservation of whales.